The future of staff groups : daring to distribute power and capacity - Henning, Joel P., 1939- (Berrett-Koehler Publishers, 1997)
The Future of Staff Groups confronts the past, faces current bottom-line demands, and describes roles for the future that can effectively reposition staff groups within their organizations. It challenges both executive management and the staff groups in all types of organizations to re-invent their roles. It confronts staff groups with the need to change the relationship they have with their corporate clients and colleagues. It further provides clear-cut steps that staff groups can take to develop new expertise that will have a clear impact on the results of the business. The Future of Staff Groups focuses squarely on the substance and content of staff groups' contribution to the organization. It is a relevant reference for all those who sell professional expertise and care about the impact they make.